Korelasi Keaktifan Siswa Dalam Kegiatan Ekstrakurikuler Terhadap Prestasi Belajar Siswa Kelas V SD 2 Karangbener - Lita Nala Karimah; Sunaisah Sunaisah; Siska Veronica Marta Alfina; Sania Nuranisa Fitriana; Sekar Dwi Ardianti; Erik Aditia Ismaya (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the relationship between student activities and learning outcomes in extracurricular activities for Class V students at SD 2 Karangbener using a sample of 10 students. The data collection techniques used in the research were questionnaires and documentation. The research results show that there is a relationship between student participation in extracurricular activities and academic success. From the test data results, there is a relationship between extracurricular activities and the learning outcomes of class V students at SD 2 Karangbener, with a correlation coefficient of 0.647 and a correlation coefficient of 41.9%.